The Subjectivity of Forced-migrant in Poems of and by Refugees - Rahayu, Nurhadianty (Universitas Sanata Dharma, 2020)
Refugeesâ€™Â perilous experiences force them to flee home for safety. Their arrival from home country toÂ theÂ host country is not only often reduced to beÂ aÂ statistical number in factual reports but also seen as threats to national well-being. The study aims to provide the argument that poems provide a symbol of resistance towards refugeesâ€™Â given fate,Â and offer a platform for them to create their authentic version of knowledge.Â Poems are chosen to be analyzed in this study as they can mediate the refugeesâ€™Â unique experiences and their struggle to cope with the changing condition. The study argues that poemsÂ of and by refugees can serve as strategic means of preserving memories that connect them with their past,Â which shape their present andÂ constructÂ an alternative subjectivity against objectification and stereotypes pinned to them. PoemsÂ analyzed in this researchÂ areÂ â€˜Homeâ€™Â byÂ WarsanÂ Shire,Â â€˜The Icebreakerâ€™Â byÂ YovankaÂ PaqueteÂ Perdigao,Â andÂ â€˜Empathyâ€™Â by A.E. Stallings. Those excerpts areÂ interpretedÂ through Feminist Refugee Epistemology (FRE),Â which according to Espiritu (2018),Â â€œreveals the hidden political forces within the site of intimate domestic interaction in each refugeeâ€™s unique experiences and queer sociality.â€Â The study concluded that poemsÂ of and by refugees couldÂ facilitate the forced-migrantsâ€™Â aspiration and create alternativeÂ knowledgeÂ as opposedÂ to their common objectification in mass-media reports.Â